Lost in transition? Modernization, formal education and violence in Karamoja. (October 2022) - Datzberger, Simone
Highlights: How formal education is designed, redistributed, governed and imposed led to multiple forms of violence against pastoralists in Karamoja. Formal education justifies and increases processes of stability (e.g. sedentarization) in an environment of high environmental variability. There is an urgency to rethink the purpose and potential of formal education in contexts of high variability such as Karamoja. More reflection is needed to consider the harm formal education can cause (and has already caused) to marginalized and non-western societies. There is a need to build on, expand and re-invest in locally developed, flexible and alternative modes of education. Abstract: There is a shift from pastoralism towards agro-pastoralism and systematized agricultural production in Karamoja, a sub-region of Uganda. At the same time, aid agencies and the government want to formally educate the Karamojong, in line with global education norms and policies. This creates a lot of ambiguities and in-betweens for the Karamojong as formal education impels sedentarization and socio-economic division. The Karamojong have a long history of using resistance to formal education as a tool to protect their pastoralist lifestyle and cultural values. This paper sheds light on the complex and often violent intersections of modernization, development and formal education. It argues that while formal education has delivered some benefits to the Karamojong, it has also led to multiple forms of violence, aid paradoxes and dead ends. The Karamojong's relationship with formal education is shaped by resistance, cultural repression, irrelevance and structural violence. If pastoralism ought to be invigorated in Karamoja, there is an urgency to rethink the purpose and potential of formal education in the region. This includes to build on, expand and re-invest in locally developed, flexible and alternative learning programmes that are more suited to fit the everyday lives and realities of the Karamojong.